Effects of age, medication, and illness duration on the N-acetyl aspartate signal of the anterior cingulate region in schizophrenia - Ende, Gabriele; Braus, Dieter F.; Walter, Sigrid; Weber-Fahr, Wolfgang; Soher, Brian; Maudsley, Andrew A.; Henn, Fritz A. (Schizophrenia research, 2000)
The authors performed a MRSI study of the anterior cingulate gyrus in 19 schizophrenic patients under stable medication and 16 controls in order to corroborate previous findings of reduced NAA in the anterior cingulate region in schizophrenia. Furthermore, correlations between NAA in the anterior cingulate gyrus and age or illness duration have been determined. A decreased NAA signal was found in the anterior cingulate gyrus of patients compared to controls. Subdividing the patient group into two groups depending on medication revealed that the group of patients receiving a typical neuroleptic medication showed a lower mean NAA in comparison to the group of patients receiving atypical antipsychotic drugs. No significant group differences in the creatine and phosphocreatine signal or the signal from choline-containing compounds were found. The NAA signal significantly correlated with age, and therefore, individual NAA values were corrected for the age effect found in the control group. The age-corrected NAA signal in schizophrenia correlated significantly with the duration of illness. The detected correlations of NAA decrease with age and illness duration are consistent with recent imaging studies where progressing cortical atrophy in schizophrenia was found. Further studies will be needed to corroborate a possible favorable effect of atypical antipsychotics on the NAA signal.
Gesehen am 12.11.2020